PERKEMBANGAN DAN GAMBARAN ANATOMIS LARVA INFEKTIF (L3) Haemonchus contortus YANG DIBIAKKAN DENGAN VERMICULLITE (Development and Anatomical Description of Infektive Larvae (L3) Haemonchus contortus Cultured with Vermicullite) - Muhammad Hambal; Rahmi Sulastri Mukhtar; Muhammad Hanafiah; Yudha Fahrimal; Winaruddin Winaruddin; Zakiah Heryawati Manaf (Jurnal Medika Veterinaria, 2016)
This study was aimed at obtaining basic information about bioecology of Haemonchus contortus, related to larval development and anatomical description of infective larvae (L3). In this study, the ova of Haemonchus contortus were harvested out of the intestines of goats, those were slaughtered in municipal slaughterhouse in Kampung Jawa Banda Aceh. The ova of Haemonchus contortus were then cultured using vermiculite as media, and observed daily until the larvae reached 3rd stage larvae. The result revealed that the larvae need 7 days to reach from eggs into infective larvae. Larvae obtained has uniform morphology, with a body diameter of 22 μm, tail length up to 55 μm hyaline, esophagus posterior to the tail of 592 μm, length of esophagus anterior to posterior esophagus 145 μm, and a total body length of larvae 737 μm.